2018
DOI: 10.1371/journal.pone.0206542
|View full text |Cite
|
Sign up to set email alerts
|

miR-21, miR-99b and miR-375 combination as predictive response signature for preoperative chemoradiotherapy in rectal cancer

Abstract: IntroductionPreoperative chemoradiotherapy (CRT) is a standard treatment for locally advanced rectal cancer patients. Despite the benefits of CRT, its use in non-responder patients can be associated with increased toxicities and surgical resection delay. The identification of CRT response biomarkers, such as microRNAs, could improve the management of these patients. We have studied the microRNA expression in pretreatment endoscopy biopsies from rectal cancer patients treated with CRT to identify potential micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 45 publications
0
36
0
2
Order By: Relevance
“…27 In recent years, it has been found that a variety of miRNAs are imbalanced in RC, which may have dual effects of tumor inhibition and cancer promotion in the mechanical regulation of RC. 28,29 As a member of miRNAs, previous studies have found that miR-1224-5p was dysregulated in diversified cancers and diseases, including RC. Mosakhani N et al found that down-regulation of miR-1224-5p resulted in a significant decline in survival rate in patients with metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…27 In recent years, it has been found that a variety of miRNAs are imbalanced in RC, which may have dual effects of tumor inhibition and cancer promotion in the mechanical regulation of RC. 28,29 As a member of miRNAs, previous studies have found that miR-1224-5p was dysregulated in diversified cancers and diseases, including RC. Mosakhani N et al found that down-regulation of miR-1224-5p resulted in a significant decline in survival rate in patients with metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Campayo and collaborators also identified miR-375, together with miR-21 and miR-99 as miRNAs related to nCRT response [ 68 ]. In particular, receiver operating characteristic (ROC) curve analyses evidenced the potential clinical utility of the combination of low levels of expression of these three miRNAs to distinguish patients with complete response (TRG 4) from patients without response or minor response (TRG 0–1) to nCRT [ 68 ].…”
Section: Micrornas In Locally Advanced Rectal Cancermentioning
confidence: 99%
“…In the validation phase, miR-99b, miR-21, and miR-375 act as chemoradiotherapy response-related miR whereas miR-328 and let-7e emerge as prognostic markers for disease-free survival and overall survival. ROC curve analysis revealed that the combination of miR-21, miR-99b, and miR-375 had the best capacity to distinguish patients with maximum response (TRG4) from others ( Campayo et al, 2018 ).…”
Section: Theranostic Value Of Mir In Rectal Cancermentioning
confidence: 99%